Internalisasi Nilai-Nilai Karakter dalam Petuah Sumbang Duo Baleh Bagi Mahasiswi Asal Minangkabau di Kota Purwokerto Tahun 2016 - Islami, Nisa (International Conference of Moslem Society, 2016)
This study used a qualitative approach which aims to find the process of internalization of the character education value through sumbang duo baleh on the Minang students in Purwokerto. The results showed: (1) Students Minang know and understand twelve ethics contained in sumbang duo baleh. (2) Through the student community the Minang value trying preserved and maintained as a manifestation of their love of Minang culture. (3) To actualize the ethical values on the basis of daily awareness of the positive values contained in sumbangduo baleh so that they can distinguish between good and bad. (4) Due to the openness of education for women can be a net gain as well as challenges to face the modernization and become a factor of a shifting values for Minangkabau students, therefor understanding and applicating of sumbang duo baleh became faded.